STRATEGI PEMASARAN BANK SYARIAH DALAM MENINGKATKAN MINAT GENERASI MILENIAL MELALUI MEDIA SOSIAL - Wahyuni, Wahyuni; Fasa, Muhammad Iqbal (Jurnal Ilmiah Ekonomi, Manajemen dan Syariah, 2024)
This research aims to explore the marketing strategies implemented by Islamic banks to increase the interest of the millennial generation through the use of social media. The millennial generation, known as the digital generation and very connected to technology, is a potential target market for the banking sector, especially sharia banks. However, to attract millennials, Islamic banks must be able to adapt to their digital preferences and behavior. Through a literature study approach and secondary data analysis, this research identifies effective marketing strategies in increasing millennial engagement. The research results show that social media can be a very effective platform if used with the right approach, such as creating educational content, collaborating with influencers, and implementing interactive campaigns. In addition, this research underlines the importance of a deep understanding of millennial consumer behavior and the challenges faced by Islamic banks in communicating sharia values ​​that are relevant to this generation. This research provides recommendations for Islamic banks in maximizing digital marketing strategies to attract the interest of the millennial generation.